Adapted version of the Pubertal Development Scale for use in Brazil - Sabine Pompéia; Gislaine de Almeida Valverde Zanini; Rafaella Sales de Freitas; Luanna Maristella Cabanal Inacio; Flávia Calanca da Silva; Giovana Ribeiro de Souza; Maria Sylvia de Souza Vitalle; Sheila Rejane Niskier; Hugo Cogo-Moreira
ABSTRACT OBJECTIVE To determine whether scores in an adapted version of the self-assessment Pubertal Development Scale into Portuguese match those from the gold standard in pubertal development (Tanner scale). METHODS This was a cross-sectional study with a convenience sample of 133 children and adolescents aged nine to 17 years (59 males; mean age of 13 years and six months, with standard deviation = 25 months). Youngsters completed the Pubertal Development Scale and were then examined by specialists in adolescent medicine. RESULTS Exact absolute agreement of pubertal stages were modest, but significant associations between measures (correlation; intra-class correlation coefficients of consistency) showed that the Pubertal Development Scale adequately measures changes that map onto pubertal development determined by physical examination, on par with international publications. Furthermore, scores obtained from each Pubertal Development Scale question reflected adequate gonadal and adrenal events assessed by clinical ratings, mostly with medium/high effect sizes. Latent factors obtained from scores on all Pubertal Development Scale questions had excellent fit indices in Confirmatory Factor Analyses and correlated with Tanner staging. CONCLUSIONS We conclude that self-assessment of body changes by youngsters using the Portuguese version of the Pubertal Development Scale is useful when estimates of pubertal progression are sufficient, and exact agreement with clinical staging is not necessary. The Pubertal Development Scale is, therefore, a reliable instrument for use in large-scale studies in Brazil that aim at investigating adolescent health related to pubertal developmental. The translated version and scoring systems are provided.